Using Generic Imagery and Groups to Encourage Student Dialogue - K. Shelley Price-Jones; Adrian M. Smith (Crossings, 2017)
This paper evaluates the ongoing effectiveness of a set of EFL classroom materials for use in groups, which were developed to encourage student dialogue in Korean General English university classes. The analysis draws upon retrospective student surveys: two solely quantitative, and one having qualitative, components. This specific lesson was part of the regular curriculum, and taught in exactly the same procedural manner for each research period; utilizing time-efficient social group rotations in combination with innovative materials partially composed of conceptual artwork. By incorporating local culture into the artefacts’ design, students were required to use language in context, and were able to personally relate to the topic through the process of combining concepts with their own funds of knowledge. The student data confirmed that this particular type of personally engaging process used at the beginning of the semester had overall positive effects on student confidence and speaking levels, along with showing evidence of learning. As such, a model is proposed with specific tasks and methodology that may inform English language teachers in other countries of an effective lesson and materials’ design.